COMBINED EFFECT OF HORSE GRAM AND FENUGREEK SEED POWDERS IN HIGH FAT-HIGH SUCROSE DIET-INDUCED PRE-DIABETES IN RATS - R, PADMAVATHI; G, SOUMYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to investigate the combined effect of horse gram (HG) and fenugreek (FG) seed powders in high fat-high sucrose (HFHS) diet-induced pre-diabetes in rats. Methods: Wistar rats (140–200 g) of either sex were randomly divided into four groups (n=6). Group 1, normal control, received normal pellet diet; Group 2, pre-diabetic control, received HFHS diet; Group 3, prophylactic group, received HFHS diet along with HG (200 mg/kg) and FG (200 mg/kg) combination; and Group 4, therapeutic group, received HFHS diet for 9 weeks followed by HG (200 mg/kg) and FG (200 mg/kg) combination for 28 days. Fasting blood glucose, lipid profiles, and OGTT were carried out on the 9th week in Group 1, Group 2, and Group 3, and at the end of the study in Group 1, Group 2, and Group 4. Results: Treatment with HFHS diet for 9 weeks has significantly increased fasting blood glucose and lipid profiles in the pre-diabetic group when compared to the normal control group indicating induction of pre-diabetes in the pre-diabetic group. In the prophylactic group, horse gram and fenugreek are given simultaneously with HFHS has significantly decreased fasting blood glucose, lipid profiles when compared to the pre-diabetic group. In the therapeutic group, treatment was given after induction of pre-diabetes for 28 days. In the therapeutic group, there was a significant decrease in fasting blood glucose, lipid profiles compared to the pre-diabetic group. Conclusion: HFHS diet-induced pre-diabetes or insulin resistance is an effective model to study and evaluate various new therapeutic modalities. The findings of the present study suggest that consumption of FG and HG as food supplements could reduce the risk of getting diabetes and progression of pre-diabetes to diabetes.